Enhancing the Effectiveness of Islamic Education through Quality Management Practices in Schools - Kamaruddin Rasyid; Siti Julaiha (Journal of Educational Management Research, 2025)
This study aims to evaluate the quality management of Islamic Education (PAI) learning at school. In the face of modernization and globalization, enhancing the quality of education is essential. This research employs a qualitative method, focusing on PAI teachers and students across various class levels as the study's subjects. Data collection techniques include interviews, observations, and documentation. The findings indicate that the quality management of PAI learning at school has been well-implemented in terms of planning, execution, and supervision. However, improvements are still needed in the organizational aspect to optimize and ensure the sustainability of the educational quality. The results of this study suggest that schools should focus on strengthening organizational management to improve the long-term quality of PAI learning and ensure its ongoing development.